2012
DOI: 10.1111/bjh.12000
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine compared with chlorambucil in previously untreated patients with chronic lymphocytic leukaemia: updated results of a randomized phase III trial

Abstract: SummaryThe efficacy of bendamustine versus chlorambucil in a phase III trial of previously untreated patients with Binet stage B/C chronic lymphocytic leukaemia (CLL) was re-evaluated after a median observation time of 54 months in May 2010. Overall survival (OS) was analysed for the first time. At follow-up, investigator-assessed complete response (CR) rate (21Á0% vs 10Á8%), median progression-free survival (21Á2 vs 8Á8 months; P < 0Á0001; hazard ratio 2Á83) and time to next treatment (31Á7 vs 10Á1 months; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 17 publications
2
64
2
1
Order By: Relevance
“…Beside the documentation of cytogenetic high-risk features and unmutated IGHV status in all enrolled patients, the clinical behavior was unequivocally aggressive, with refractoriness to standard treatments (including 31% fludarabine refractory) and/or responses to previous therapies lasting <24 months. Bendamustine, in combination with rituximab, is a treatment of choice in older patients with CLL [13], but its efficacy in patients with high-risk disease (i.e., 17p deletion) was quite low [16]. In a recent trial in the relapsed/refractory setting, rituximab and bendamustine (RB, at a dose of 70 mg/m 2 combined with rituximab at standard doses) achieved an OR of 59% in a cohort of 72 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the documentation of cytogenetic high-risk features and unmutated IGHV status in all enrolled patients, the clinical behavior was unequivocally aggressive, with refractoriness to standard treatments (including 31% fludarabine refractory) and/or responses to previous therapies lasting <24 months. Bendamustine, in combination with rituximab, is a treatment of choice in older patients with CLL [13], but its efficacy in patients with high-risk disease (i.e., 17p deletion) was quite low [16]. In a recent trial in the relapsed/refractory setting, rituximab and bendamustine (RB, at a dose of 70 mg/m 2 combined with rituximab at standard doses) achieved an OR of 59% in a cohort of 72 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bendamustine is an alkylating agent that has purine analogue properties and exhibits considerable activity in indolent lymphomas and CLL [13,14]. It has been reported that bendamustine exerts a cytotoxic effect in CLL cell lines, involving both p53-dependent and p53-independent mechanisms [15].…”
Section: Introductionmentioning
confidence: 99%
“…As both age and mutation status are prognostic indicators and potential treatment-effect-modifiers in CLL [6], analyses were conducted, where data permitted, on the subgroups of patients aged ≥65 years, those with unmutated IgVH, those with del11q mutation and those without del17p mutation. Some or all outcomes of interest for the four subgroups were available from four RCTs: RESONATE-2 [13], CLL11 [12], COMPLEMENT1 [19] and Knauf et al [23]. Pairwise comparisons were conducted for ibrutinib versus Obi-Chl, R-Chl, Ofa-Chl and bendamustine, respectively, and effects were tested in the subgroups for which data were available.…”
Section: Regression Analyses For Survival Outcomes Using Chlorambucilmentioning
confidence: 99%
“…Single agent therapy with chlorambucil, cyclophosphamide or with fludarabine, lenalidomide, bendamustine was tested in different clinical trials in the past and is no longer considered as the standard therapeutic modality in CLL but is used in resource poor countries due to its low cost. In randomized trials, single agent fludarabine or bendamustine have shown significant improvement over chlorambucil alone [57,58]. Combination of fludarabine with cyclophosphamide (FC) or cladribine with cyclophosphamide (CC) has shown improvement in the overall response rate (ORR) and progression free survival (PFS) compared to single agent therapy [59][60][61].…”
Section: Evolution Of Treatment Of Cll (Then and Now In 2016)mentioning
confidence: 99%